Revolutionary Love as Shared Interreligious Comparative Category: Christian Engagements with Engaged Buddhism and Gandhian Nonviolence - Thatamanil, John J. (Toronto journal of theology, 2017)
Is revolutionary love a narrowly Christian category inappropriate as a theme for the American Academy of Religion? This paper argues no. Revolutionary love can be reconfigured as a vague interreligious category. This paper does that conceptual work and then proceeds to show that both Engaged Buddhists and Gandhian Hindus can recognize revolutionary love as a meaningful category for their communities and traditions. By demonstrating that revolutionary love is no merely Christian category, this paper suggests that the theme is not only appropriate for a body such as the AAR but can also help those groups within the AAR that are interested in normative conversation across religious boundaries to have those conversations.